Heydar Aliyev’s Views on the Development of Azerbaijan’s Relations with Türkiye - Ramile Dadaşova (Avrasya İncelemeleri Dergisi)
The historical relations between Azerbaijan and Türkiye, marked by shared language, religion, and customs, have deep roots. National leader Heydar Aliyev stated that following the collapse of the Soviet Union, Türkiye had a crucial role to play in embracing the legacy of Gazi Mustafa Kemal Atatürk, particularly in developing and nurturing Turkish states. Aliyev believed that Türkiye could leverage its global influence to support Azerbaijan’s international relations and engage with major powers. Notably, he emphasized the importance of the Heads of Turkic States summits, a collective assembly of the Turkic republic, in fostering closer relations among Turkic countries. Aliyev also placed great emphasis on the development of Azerbaijan’s diaspora abroad, the educational pursuit of Azerbaijani students abroad, and the development of relations between professors and teachers working abroad. He preferred the development of economic relations with Türkiye from the economic perspective and the perspective of strengthening our brotherhood.